An Unusual Case of Cushing’s Syndrome: Coexistence of Functional Pituitary and Adrenal Adenoma - Muzaffer İlhan; Özcan Karaman; İrem Yasin Çetin; Nur Büyükpınarbaşılı; Jamshid Hamdard; Ertuğrul Taşan (Haseki Tıp Bülteni, 2017)
A case of adrenocorticotropic hormone (ACTH)-independent Cushing’s syndrome, which develops in the course of ACTH-dependent Cushing’s disease, is presented in this report. A 47-year-old woman with a past history of surgery and gamma knife radiosurgery because of Cushing’s disease was admitted to the endocrinology clinic with weight gain and unregulated blood glucose levels. Hypercortisolemia was still persisting and diagnostic work-up indicated ACTH-independent Cushing’s syndrome. Along with the rare possibility of this coexistence, longstanding ACTH hypersecretion can play a role in functional transition of adrenal adenomas. Further studies are needed to clarify the underlying mechanisms.